TH9, TH17, and TH22 Cell Subsets and Their Main Cytokine Products in the Pathogenesis of Colorectal Cancer - Cui, Guanglin (Frontiers in Oncology, 2019)
In recent years, several newly identified T helper (TH) cell subsets, such as TH9, TH17 and TH22, and their respective cytokine products, IL-9, IL-17 and IL-22, have been reported to play critical roles in the development of chronic inflammation in the colorectum. Since chronic inflammation is a potent driving force for the development of human colorectal cancer (CRC), the contributing roles of TH9/IL-9, TH17/IL-17 and TH22/IL-22 in the pathogenesis of CRC have recently become an increasingly popular scientific area of investigation. Extensive laboratory and clinical evidence suggests a positive relationship between these new TH subsets and the growth and formation of CRC, whereas administration of IL-9, IL-17 and IL-22 signal inhibitors can significantly alter the formation of colorectal chronic inflammation or CRC lesions in animal models, suggesting that blocking these cytokine signals might represent promising immunotherapeutic targets. This review summarized recent findings and currently available data for understanding the vital role and therapeutic significance of TH9/IL-9, TH17/IL-17 and TH22/IL-22 in the development of colorectal tumorigenesis.